Small Enterprise Finance under Liberalization in Ghana - Aryeetey, Ernest; Baah-Nuakoh, Amoah; Duggleby, Tamara; Hettige, Hemamala; Steel, William F. (World Bank, Washington, DC, 2012)
This study investigates the apparent contradiction between the high propensity of small- and medium-sized enterprises (SMEs) to identify finance as their primary constraint and the view of banks that SME lending remains low in part for lack of bankable demand. Surveys were conducted of relatively successful microenterprises and SMEs to assess demand and sources of finance, and formal and informal financial institutions were interviewed to analyze constraints on the supply side. The survey results show that credit for start-up is rare and that the smaller the enterprise, the greater the equity finance share of the initial investment. Many SMEs achieve substantial growth through reinvestment of profits, making it difficult to conclude that entry and growth of SMEs depends crucially on loans. Other forms of finance, such as customers' advances and supplier's credit are at least as important as bank credit. Nevertheless, the evidence suggests that exploitation of highly profitable opportunities by SMEs could be accelerated if they had greater access to external financing. Tight money, banks' efforts to improve portfolio performance, centralization of decision-making, and lack of competition explain why banks have shown little interest in developing SMEs as a market niche. The study suggests techniques that banks could adopt to overcome the problems of high transaction costs and risks in SME lending, drawing on the methods of informal financial agents.